Penerapan Strategi Direct Instruction dalam Mengatasi Kesulitan Belajar Membaca Al-Qur’an - Abdul Muthalib; Melati Chamariah; Niza Fadila (Hikmah, 2023)
Teachers must have the ability to choose and determine unique strategies to optimize students' abilities when learning. Especially in learning the Koran, because not a few students have difficulty reading the Koran. This study aims to eliminate various difficulties and obstacles experienced by students when studying the Qur'an. This research has implications for correcting students' mistakes in reading the Qur'an and being a solution for teachers in overcoming difficulties in learning the Qur'an for students. Researchers used classroom action research methods. The use of the direct instruction strategy in this study requires a demonstration method, especially by using the talaqqi technique which functions to improve students' reading of the Qur'an individually so that the results are maximized. From the results of this study, the authors obtained the results of improving students' Al-Qur'an learning abilities after using the direct instruction strategy, namely, (1) In the pre-cycle learning outcomes students who completed were 2 students and those who did not complete were 23 students with an average score 67.16 (2) In cycle 1, there were 10 students who completed and 15 students who did not complete with an average score of 78.4 (3) In cycle 2, students who completed 23 students and who did not complete were 2 students with average value of 90.96. This proves that the direct instruction strategy is effective in overcoming students' difficulties in learning to read the Qur’an.